Labor market structure and offshoring. Issue 4 (22nd March 2020) - Shin, Sangwha; Davidson, Carl
Abstract: We consider a two‐country, two‐sector model in which a firm's offshoring decision depends on labor market rigidities that impose additional costs on the firm. Firms endogenously choose their organizational form considering their productivity level and organizational costs. The costs generated by labor market frictions play a key role in determining the benefits of each organizational structure, and thus helps determine the conditions under which a firm decides to offshore. There are three different types of equilibria depending on the relative levels of the domestic and foreign labor market costs and the price of the intermediate input. In all equilibria, a relative rise in the domestic labor market cost increases the share of firms that offshore, while decreasing domestic integration. Furthermore, an economy with offshoring has a higher welfare level and a lower unemployment rate than it would under autarky.